2021
DOI: 10.1002/bse.2920
|View full text |Cite
|
Sign up to set email alerts
|

When are entrepreneurs more environmentally oriented? An analysis of stakeholders' pressures at different stages of evolution of the venture

Abstract: Entrepreneurs are subjected to increased institutional pressures that encourage them to include environmental issues in their overall business objectives. Despite this, entrepreneurs do not always place the same importance on environmental issues in the overall objectives, but some are more environmentally oriented than others. We contend that these differences are explained by two factors: the stage of evolution of the venture and the intensity of coercive and normative environmental pressures on entrepreneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Studies relying on institutional theory and stakeholder theory suggested that stricter regulations improved CES because regulatory compliance provided legitimacy, while noncompliance would result in fines. While most studies found regulatory stringency to have positive significant effects (e.g., Bernal et al, 2021; Clemens & Papadakis, 2008; García‐Quevedo et al, 2020; Lozano, 2015), two studies found insignificant effects (Van et al, 2018; Zameer et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies relying on institutional theory and stakeholder theory suggested that stricter regulations improved CES because regulatory compliance provided legitimacy, while noncompliance would result in fines. While most studies found regulatory stringency to have positive significant effects (e.g., Bernal et al, 2021; Clemens & Papadakis, 2008; García‐Quevedo et al, 2020; Lozano, 2015), two studies found insignificant effects (Van et al, 2018; Zameer et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Normative influences can produce standards, ensuring appropriate behaviors on the part of members in a group (Bernal et al, 2022;Scott, 2005). Unlike explicit regulatory standards, these norms are usually implicit.…”
Section: The Moderating Role Of Normative Pressuresmentioning
confidence: 99%
“…Specifically, normative agents—for example, professional non‐governmental organizations (NGOs)—are influential actors considering institutional pressures (Berrone et al, 2013; Kassinis & Vafeas, 2006). Normative influences can produce standards, ensuring appropriate behaviors on the part of members in a group (Bernal et al, 2022; Scott, 2005). Unlike explicit regulatory standards, these norms are usually implicit.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Sustainable entrepreneurs often face the challenge of double externality (Horbach et al, 2012; Mothe et al, 2018; Rennings, 2000) and struggle to capture and appropriate the value from the goods and services they provide. They also carry the burden of the liability of smallness , the liability of newness in the marketplace (Adomako et al, 2019; Stinchcombe, 2000), and confront multiple institutional obstacles (Amorós et al, 2019; Bernal et al, 2022; Danso et al, 2019; Esposito et al, 2022). As a result, adopting a sustainability orientation in entrepreneurial ventures is considered costly, risky, and taxing on the ability of the firm to survive in the market, reach profitability, and grow (Fernández‐López et al, 2022).…”
Section: Introductionmentioning
confidence: 99%